Acceleration of high charge-state target ions in high-intensity laser interactions with sub-micron targets. (17th November 2016) - McGuffey, C; Raymond, A; Batson, T; Hua, R; Petrov, G M; Kim, J; Krauland, C M; Maksimchuk, A; Thomas, A G R; Yanovsky, V; Krushelnick, K; Beg, F N
Abstract: We have studied laser acceleration of ions from Si3 N4 and Al foils ranging in thickness from 1800 to 8 nm with particular interest in acceleration of ions from the bulk of the target. The study includes results of experiments conducted with the HERCULES laser with pulse duration 40 fs and intensity 3 × 10 20 W cm −2 and corresponding two-dimensional particle-in-cell simulations. When the target thickness was reduced the distribution of ion species heavier than protons transitioned from being dominated by carbon contaminant ions of low ionization states to being dominated by high ionization states of bulk ions (such as Si 12+ ) and carbon. Targets in the range 50–150 nm yielded dramatically greater particle number and higher ion maximum energy for these high ionization states compared to thicker targets typifying the Target Normal Sheath Acceleration (TNSA) regime. The high charge states persisted for the thinnest targets, but the accelerated particle numbers decreased for targets 35 nm and thinner. This transition to an enhanced ion TNSA regime, which more efficiently generates ion beams from the bulk target material, is also seen in the simulations.